Implementation of flare-out situation with restructure-riffler-branch-dot on diffusiveness fluctuation of fabricated function material-object on porous of stratified epithelium - Kang, Geon-Uk; Park, Beom-Seok; Kim, Jeong-Lae (Edelweiss Applied Science and Technology, 2025)
A technique for determining flare-out fluctuation in stratified epithelium cells that maintain a resonance state with a riffler-branch-dot pattern is identified by the instantaneous recognition rate (IRR) and distinction recognition rate (DRR). We aim to produce a form of flare-out perceptibility that identifies the conditions regulating the perceptibility rate in a diffusiveness resonance system. In stratified epithelium cells, fluctuation takes the shape of a riffler-branch-dot, so we decided to search for a diffusiveness-down structure according to the flare-out situation layer, and a flare-out porous value appeared. In the flare-out porous, the awareness rate concept has a flare-out resonance function, so the fluctuation signal appeared to confirm the instantaneous velocity and vacuum velocity. The flare-out fluctuation of IRR-DRR confirmed that the flare-out resonance function in porous showed a maximum-minimum value. In the flare-out resonance situation, the fluctuation was found to be the flare-out porous value. Wr-af-FA-αMAX-MIN is far fluctuation of 17.19±3.43 units, Wr-af-CO-αMAX-MIN is convenient fluctuation of 6.11±1.18 units, Wr-af-FL-αMAX-MIN is flank fluctuation of 2.32±0.63 units, and Wr-af-VI-αMAX-MIN is vicinage fluctuation of 0.36±0.05 units. Diffusiveness resonance in stratified epithelium cells can be confirmed by the ability of IRR-DRR to estimate the flare-out resonance function with the coarse degree awareness rate by calculating the coarse transient discrimination function represented by the awareness rate system. We can estimate the morphology of the flare-out porous through the vacuum signal, and we can estimate the diffusivity data of the diffusivity resonance rate through the diffusivity awareness system.